2003
DOI: 10.1136/heart.89.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive cardiac rehabilitation programme for implantable cardioverter-defibrillator patients: a randomised controlled trial

Abstract: Objective: To investigate the effects of a 12 week comprehensive cardiac rehabilitation (CCR) programme on patients who have undergone implantation of an implantable cardioverter-defibrillator (ICD). Design: Sixteen patients with ICDs (14 (88%) male, mean (SD) age 58 (10) years, range 34-74 years) were randomised to either attend an individually tailored CCR programme or receive usual care. They then changed to the alternative regimen for a further 12 weeks. Exercise capacity was assessed using a treadmill exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 31 publications
5
164
0
5
Order By: Relevance
“…49 Exercise may be viewed as a safe exposure to fear that leads to successive advances at returning to a full range of lifestyle and activities. Fitchet et al 50 compared the effects of a cardiac rehabilitation program with ICD patients including exercise, education, and psychotherapy (12 weeks) with usual care. Exercise time improved 16%, with no ventricular tachycardia or shocks.…”
Section: Standard Cardiac Management Plus Cardiac Rehabilitationmentioning
confidence: 99%
“…49 Exercise may be viewed as a safe exposure to fear that leads to successive advances at returning to a full range of lifestyle and activities. Fitchet et al 50 compared the effects of a cardiac rehabilitation program with ICD patients including exercise, education, and psychotherapy (12 weeks) with usual care. Exercise time improved 16%, with no ventricular tachycardia or shocks.…”
Section: Standard Cardiac Management Plus Cardiac Rehabilitationmentioning
confidence: 99%
“…no difference in adverse events). Data on exercise within the ICD population seems to support its safety as well as efficacy [9,17,30,32,33,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…15 (3573 participants) [9,[18][19][20][28][29][30][31][32][33][34][35][36][37][38] studies collected data relevant to our outcomes of interest, specifically safety and/or adverse events during and/or after ET. Of these studies, 10 were examined by meta-analyses (3171 participants) [9,19,20,28,30,32,33,36,37,39] as they included a comparator control group: 7 studies (2498 participants) [9,28,30,32,33,36,37] used non-ET ICD controls compared to ET-ICD patients and 3 studies (673 participants) [19,20,38] used ET non-ICD patients compared to ET-ICD patients. Of the 10 studies, 7 had data relevant only to our primary outcome.…”
Section: Literature Searchmentioning
confidence: 99%
“…However, ET with an appropriate prescription and careful supervision, rather than restriction of exercise, may be the recommended course of treatment for these patients, because cardiac rehabilitation with ET has been reported to improve exercise capacity and quality of life in patients with ICDs. 16 Webb-Peploe et al demonstrated that complications from ET were more common in patients with ischemic cardiomyopathy, larger LV diameters, reduced fractional shortening, earlier peak mitral flow, lower exercise tolerance, and greater ventilation drive at baseline. 7 Although the present results, which show that a larger LV diameter, lower exercise tolerance, and greater ventilation drive were predictors of CE, agree with the results reported by Webb-Peploe et al, an ischemic origin and reduced LV contractile function were not identified by us as significant predictors of CE.…”
Section: Previous Studiesmentioning
confidence: 99%